BENTUK-BENTUK DAN PERLINDUNGAN KONSERVASI SUMBER DAYA ALAM HAYATI DI INDONESIA - Nicky Novita, Kadek; Parikesit Widiatedja, I Gst. Ngr. (Kertha Negara : Journal Ilmu Hukum; Vol. 02, No. 04, Juni 2014)
Natural resources shall be considered as a highly essential element in an ecosystem. Each components of natural resources and its ecosystem shall be interdependent and its exploitation shall impacts adversely on twofold, thus, any deterioration shall also lead to the disruption of ecosystem. Hence, a means of conservation as a management tool of natural resources both in situ and ex situ is highly prerequisite. Pursuant to Law No 5 of 1990, such means of protection and conservation are regulated. This writing is composed by utilizing normative legal research and statutory approach in its methodology. It is expected that protection of conservation to be enforced in Indonesia to prevent breach of conduct from regulation stipulated which later triggered the application of penal sanction.
Keywords: Natural Resources, Conservation